Xavier Mina. Proclamas y otros escritos - Ortu´ño Martínez, Manuel (Huarte de San Juan. Geografía e Historia, 1999)
A very interesting fact related to the Spanish American rebellion took place during the second decade of the XIX century, at the end of the Napoleonic wars. The protagonist was Xavier Mina a young liberal soldier born in Navarre, ignored by the Spanish historiography. With the support of the Spanish liberal exiles and Americans living in London, Xavier Mina organized an international expedition that acted throughout the year 1817, helping the Mexicans rebels. He was aided by English Whigs, Lord Holland, Lord Russell and the City merchants. In the course of the Expedition, Xavier Mina made some manifestos summing up his ideological and political positions, which represented an attitude of radical liberalism unknown up to date. Other writings are published as well as of his military reports, which show his reactions and the way he faced his unfortunate fate.